Рассказы и сказки - Бианки Виталий Валентинович (Школьная библиотека, 2019)
Экземпляры: (20210708) / Инвентарный номер: 41777 / Цена: 411.62 / Сис.шифр: 84(2=411.2)6 / Авт.знак: Б 59 / ГРНТИ: 17 / ББК: 84(2=411.2)6